Prevalence of Masked Hypertension and Its Association With Subclinical Cardiovascular Disease in African Americans: Results From the Jackson Heart Study. Issue 3 (29th March 2016) - Redmond, Nicole; Booth, John N.; Tanner, Rikki M.; Diaz, Keith M.; Abdalla, Marwah; Sims, Mario; Muntner, Paul; Shimbo, Daichi
Abstract : Background: Studies consisting mostly of whites have shown that the prevalence of masked hypertension differs by prehypertension status. Using data from the Jackson Heart Study, an exclusively African American population‐based cohort, we evaluated the association of masked hypertension and prehypertension with left ventricular mass index and common carotid intima media thickness. Methods and Results: At the baseline visit, clinic blood pressure (CBP) measurement and 24‐hour ambulatory blood pressure monitoring were performed. Masked hypertension was defined as mean systolic/diastolic CBP <140/90 mm Hg and mean daytime systolic/diastolic ambulatory blood pressure ≥135/85 mm Hg. Clinic hypertension was defined as mean systolic/diastolic CBP ≥140/90 mm Hg. Normal CBP was defined as mean systolic/diastolic CBP <120/80 mm Hg and prehypertension as mean systolic/diastolic CBP 120 to 139/80 to 89 mm Hg. The analytic sample included 909 participants. Among participants with systolic/diastolic CBP <140/90 mm Hg, the prevalence of masked hypertension and prehypertension was 27.5% and 62.4%, respectively. The prevalence of masked hypertension among those with normal CBP and prehypertension was 12.9% and 36.3%, respectively. In a fully adjusted model, which included prehypertension status and antihypertensive medication use as covariates, left ventricular mass index was 7.94 g/m 2 lower among those without masked hypertension compared to participants with masked hypertension ( P <0.001). Left ventricular mass index was also 4.77 g/m 2 lower among those with clinic hypertension, but this difference was not statistically significant ( P =0.068). There were no significant differences in left ventricular mass index between participants with and without masked hypertension, or clinic hypertension. Conclusions: Masked hypertension was common among African Americans with prehypertension and also normal CBP, and was associated with subclinical cardiovascular disease.